Spinal ependymoma presenting with visual and hearing impairment – An unusual sequelae - Jagathlal Gangadharan; Paritosh Pandey; Vani Santosh; Rose Dawn Bharath (Indian Journal of Neurosurgery)
Superficial siderosis of the central nervous system is a rare complication of recurrent bleeding in the neuraxis which may present with various symptoms. We report a case of spinal tumor presenting with superficial siderosis with involvement of vision and hearing along with ataxia. This is a rare presentation of superficial siderosis. The pathogenesis of selective involvement of these cranial nerves is discussed.